2000
DOI: 10.1023/a:1005577330695
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The antioxidative effect of intact cells and intracellular cell-free extracts of intestinal lactic acid bacteria B. longum (ATCC 15708) and L. acidophilus (ATCC 4356) was investigated. Both intact cells and intracellular cell-free extracts of 10(9)cells of B. longum and L. acidophilus demonstrated antioxidative activity, inhibiting linoleic acid peroxidation by 28-48%. This indicated that these two strains demonstrated excellent antioxidative activity. B. longum and L. acidophilus also showed the ability to sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(78 citation statements)
references
References 15 publications
3
75
0
Order By: Relevance
“…Free radical scavenging is one of the mechanisms by which antioxidants inhibit lipid peroxidation (32,45). An in vitro ability of Lactobacillus and Bifidobacterium to quench free radicals has been reported in a few studies as well (29,57). These data, together with our findings, suggest that the DPPh radical scavenging activity is genus-, strain-and dosedependent.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Free radical scavenging is one of the mechanisms by which antioxidants inhibit lipid peroxidation (32,45). An in vitro ability of Lactobacillus and Bifidobacterium to quench free radicals has been reported in a few studies as well (29,57). These data, together with our findings, suggest that the DPPh radical scavenging activity is genus-, strain-and dosedependent.…”
Section: Resultssupporting
confidence: 88%
“…lactis LL27 was analyzed by a modifi cation method utilized by Blois (5) and lin and chang (29). the scavenged DPPh was then monitored by measuring the decrease in absorbance at 517 nm.…”
Section: Determination Of αα-Diphenyl-β-picrylhydrazyl (Dpph)mentioning
confidence: 99%
“…Lactic acid bacteria (LAB) are often used as supplements in probiotic products. The therapeutic effects of LAB include improvement of lactose intolerance, prevention of intestinal infection, decrease in serum cholesterol, increase in immune response, anticarcinogenic activity, and antioxidative effects (Lin and Chang, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the inherent high nutritional value as a source of protein and calcium, kefir is believed to be beneficial to health in the countries where kefir is an essential part of the diet culture for a long time [26,27] . Effects of kefir on antioxidant and growth factors have been shown in several studies [22,[28][29][30][31][32][33] found that the protective effect of kefir is more than vitamin E in oxidative damage induced by CCl 4 in mice, by reducing lipid peroxidation and increasing reduced glutathione and glutathione peroxidase levels. In recent years in the mentality of a healthy diet, nutrition support with antioxidant-rich foods to prevent damages causing oxidative stress in the body has risen to the forefront.…”
Section: Discussionmentioning
confidence: 99%